2011
DOI: 10.1007/s10943-011-9556-7
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Breast Screening is Influenced by Current Religion and Religion of Upbringing

Abstract: Research has shown that individuals with a current religious affiliation are more likely to use preventive health services. The aim of this study was to determine whether breast screening uptake in Northern Ireland is higher amongst women with a current affiliation to an organised religion and, for those with no current affiliation, to examine whether their religion of upbringing is associated with uptake of breast screening. The Northern Ireland Longitudinal Study (NILS) was used to link Census and national b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…We showed that religious attendance increases the likelihood of the undertaking of a cancer screening among middle-aged and older individuals in Germany. This is in accordance with the majority of existing studies (21)(22)(23)(24). Moreover, the same pattern occurs when researchers test the relationship between religious attendance and the utilization of various kinds of preventive health care, such as physical examinations (39).…”
Section: Relation To Previous Research and Possible Explanationssupporting
confidence: 88%
See 3 more Smart Citations
“…We showed that religious attendance increases the likelihood of the undertaking of a cancer screening among middle-aged and older individuals in Germany. This is in accordance with the majority of existing studies (21)(22)(23)(24). Moreover, the same pattern occurs when researchers test the relationship between religious attendance and the utilization of various kinds of preventive health care, such as physical examinations (39).…”
Section: Relation To Previous Research and Possible Explanationssupporting
confidence: 88%
“…Regarding the differences between Catholics, Protestants, and those who are not members of any religious group, previous research reveals that Protestants are more likely to undergo breast examinations (24) as well as preventive cancer screening in general (46) for Northern Irish women. A possible explanation might be that a higher importance of the religious denomination in Northern Ireland, as Christians and Protestants were standing in conflict against each other not a long time ago, may have led to stronger differences between these subgroups.…”
Section: Relation To Previous Research and Possible Explanationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies exist that examined the link between religion or spirituality and health screening behavior [37][38][39][40][41][42][43][44][45][46] as well as mental health service utilization. [47][48][49] These studies mainly showed that these explanatory variables were associated with greater use of preventive care services, whereas they were associated with decreased utilization of professional mental health services.…”
Section: Discussionmentioning
confidence: 99%